2021
DOI: 10.3390/nano11112915
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis, Characterization, Photocatalytic Activity, and Cytotoxicity of Ag-Doped MgO Nanoparticles

Abstract: Due to unique physicochemical properties, magnesium oxide nanoparticles (MgO NPs) have shown great potential for various applications, including biomedical and environmental remediation. Moreover, the physiochemical properties of MgO NPs can be tailored by metal ion doping that can be utilized in photocatalytic performance and in the biomedical field. There is limited study on the photocatalytic activity and biocompatibility of silver (Ag)-doped MgO NPs. This study was planned for facile synthesis, characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 63 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…NPs of Ag (silver) are known for their intense toxicity and excellent antibacterial properties [ 48 , 49 ]. As expected, Ag doping significantly increased cytotoxicity of otherwise biocompatible magnesium oxide (MgO) NPs in HUVE cells according to the amount of the Ag present in the MgO-Ag nanocomposite [ 50 ]. Reports suggests that rGO NPs are less toxic than NPs of Ag alone [ 51 ].…”
Section: Discussionmentioning
confidence: 71%
“…NPs of Ag (silver) are known for their intense toxicity and excellent antibacterial properties [ 48 , 49 ]. As expected, Ag doping significantly increased cytotoxicity of otherwise biocompatible magnesium oxide (MgO) NPs in HUVE cells according to the amount of the Ag present in the MgO-Ag nanocomposite [ 50 ]. Reports suggests that rGO NPs are less toxic than NPs of Ag alone [ 51 ].…”
Section: Discussionmentioning
confidence: 71%
“…The results indicate that all elements present in the compound and the peaks of Mg, Cl, and O confirm the synthesis of Mg­(OH) 2 from the MgCl 2 ·6H 2 O precursor (Figure a–d). In addition, Cu, Na, and Au peaks were designated to the copper grid, used NaOH during synthesis as a precipitating agent, and gold coating . The carbon peak may be attributed to St/g-C 3 N 4 dopants.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen bonding between the exposed OH group on the Mg(OH) 2 and Au peaks were designated to the copper grid, used NaOH during synthesis as a precipitating agent, and gold coating. 39 The carbon peak may be attributed to St/g-C 3 N 4 dopants.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 shows a literature overview of MgO photocatalyst doped with different elements (transition metals and rare earth) for the degradation of organic pollutants from water. In references [44,45] transition metals (Fe and Ag) were used to dope MgO nanoparticles in order to improve the degradation of MB under UV light of MgO. The results showed that the 4 mol.% Fe and 2 mol.% Ag MgO NPs have achieved 88% and 75% degradation rates, respectively.…”
Section: Photocatalytic Activity Of Mgo and Er-doped Mgo Npsmentioning
confidence: 99%